Methods of synchronization of electric drives not mechanically connected - A. E. Bychkov; T. A. Funk; A. V. Aleksandrov (Омский научный вестник)
The article provides a comparative analysis of the structures of synchronization of the motion of electric drives of medium and high power. A comparison of synchronization structures is made in terms of the impact on the final operation of the system and hardware synchronization methods in terms of applicability and maximum performance. The mathematical apparatus is based on the principle of separation of the movements of each of the electric drives and the representation of its transfer function in matrix form. The control ranges and speed of different types of systems are compared experimentally by evaluating the speed of data transmission and evaluating the speed ripple at low revs.